2012
DOI: 10.1186/1472-6882-12-252
|View full text |Cite
|
Sign up to set email alerts
|

Young coconut juice can accelerate the healing process of cutaneous wounds

Abstract: BackgroundEstrogen has been reported to accelerate cutaneous wound healing. This research studies the effect of young coconut juice (YCJ), presumably containing estrogen-like substances, on cutaneous wound healing in ovairectomized rats.MethodsFour groups of female rats (6 in each group) were included in this study. These included sham-operated, ovariectomized (ovx), ovx receiving estradiol benzoate (EB) injections intraperitoneally, and ovx receiving YCJ orally. Two equidistant 1-cm full-thickness skin incisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 20 publications
3
19
0
1
Order By: Relevance
“…In contrast, women in these areas are prohibited from drinking coconut juice because it disrupts their menstrual cycle, and individuals in Java are afraid to drink coconut milk because it may diminish their fertility (18)(19)(20). It therefore seems that YCJ may exert its bone protective effects only in the presence of endogenous sex steroids, suggesting that the positive effect on bone observed 6 weeks following ovariectomy (21) were no longer apparent at 12 weeks following ovariectomy.…”
Section: Weeks 12 Weeks ---------------------------------------------mentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, women in these areas are prohibited from drinking coconut juice because it disrupts their menstrual cycle, and individuals in Java are afraid to drink coconut milk because it may diminish their fertility (18)(19)(20). It therefore seems that YCJ may exert its bone protective effects only in the presence of endogenous sex steroids, suggesting that the positive effect on bone observed 6 weeks following ovariectomy (21) were no longer apparent at 12 weeks following ovariectomy.…”
Section: Weeks 12 Weeks ---------------------------------------------mentioning
confidence: 99%
“…However, some recent transgenic studies have indicated that ERβ may serve a key role in preventing obesity and obesity-related metabolic disease (36,37). Radenahmad et al (20) demonstrated that both ERα and ERβ were highly expressed in a cutaneous wound of ovariectomized rats supplemented with YCJ, although ERα is predominantly expressed in normal skin. These findings may endorse the authors' speculation that the effects of YCJ may be exerted through ERβ.…”
Section: Weeks 12 Weeks ---------------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, young coconut juice (YCJ), defined as the juice extracted from the fruit of a 6‐month‐old coconut, has traditionally been consumed to alleviate symptoms associated with menopause by women in Thailand. Taken together, these folk remedies strongly indicate that YCJ may have phytoestrogenic effects (Radenahmad et al ., ; Radenahmad et al ., ; Radenahmad et al ., ). Indeed, Pungmatharith () demonstrated that 1 mL of YCJ contains 2.45 pg of 17ß‐estradiol along with other sex hormone‐like substances.…”
Section: Introductionmentioning
confidence: 97%
“…The active ingredient(s) of YCJ was found to be β -sitosterol [23]. YCJ was found to prevent osteoporosis [24, 25], preserve cells involved in motility of the gastrointestinal tract [26], accelerate wound healing, and improve skin complexion [27]. It was also found that YCJ at a dose of 100 ml/kg b.w./day could reduce AD pathologies in ovariectomized rats within 4 weeks.…”
Section: Introductionmentioning
confidence: 99%